Soil nitrogen sorption using charcoal and wood ash - Hamidi, Nur Hidayah; Ahmed, Osumanu Haruna; Omar, Latifah; Huck, Ywih Ch’ng (MDPI AG, 2021)
This paper reviews the use of charcoal and wood ash in acid soils as adsorbents to improve N availability at the same time improving their soil fertility and crop productivity. Soil acidification poses a major challenge in agricultural sustainability and it is serious in highly weathered soils such as Ultisols and Oxisols which are noted for nutrient deficiency and Al and Fe ions toxicities. Understanding sorption mechanisms and isotherms is important for the improvement of soil N availability particularly inorganic N. However, understanding the sorption mechanisms in relation to charcoal and wood ash as absorbents in the literature is difficult because the soil amendments vary depending on their raw materials or sources of origin. Therefore, one of the objectives of this review is to provide recent research findings and theory development on the role of charcoal and wood ash in agriculture. Furthermore, this review focuses on how charcoal and wood ash improve N availability through physical, chemical and biological processes in mineral acidic soils. Balanced application and good understanding of the role of charcoal and wood ash as soil amendments have potential benefits to improve N availability and crop productivity.